Grating network of ZnO nanostructure - Xu, Chunxiang (2011)
Through a vapor-phase transport method, a three-dimensional network nanostructure of ZnO, which is similar to the microstructures of a butterfly wing, was fabricated by using zinc powders as the source. The analysis of X-ray diffraction and energy dispersive spectra demonstrate the ZnO network covered on the surface of a Zn microball. The observation of scanning electron microscopy, high-resolution transmission microscopy, and selected area electron diffraction revealed that the ZnO backbone grew along [0001], 1010, 1101, and 1211 directions to form a three-dimensional network. The growth process was discussed in detail.